If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (11b + 9)(2b + -3) = 0 Reorder the terms: (9 + 11b)(2b + -3) = 0 Reorder the terms: (9 + 11b)(-3 + 2b) = 0 Multiply (9 + 11b) * (-3 + 2b) (9(-3 + 2b) + 11b * (-3 + 2b)) = 0 ((-3 * 9 + 2b * 9) + 11b * (-3 + 2b)) = 0 ((-27 + 18b) + 11b * (-3 + 2b)) = 0 (-27 + 18b + (-3 * 11b + 2b * 11b)) = 0 (-27 + 18b + (-33b + 22b2)) = 0 Combine like terms: 18b + -33b = -15b (-27 + -15b + 22b2) = 0 Solving -27 + -15b + 22b2 = 0 Solving for variable 'b'. Factor a trinomial. (-9 + -11b)(3 + -2b) = 0Subproblem 1
Set the factor '(-9 + -11b)' equal to zero and attempt to solve: Simplifying -9 + -11b = 0 Solving -9 + -11b = 0 Move all terms containing b to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -11b = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -11b = 0 + 9 -11b = 0 + 9 Combine like terms: 0 + 9 = 9 -11b = 9 Divide each side by '-11'. b = -0.8181818182 Simplifying b = -0.8181818182Subproblem 2
Set the factor '(3 + -2b)' equal to zero and attempt to solve: Simplifying 3 + -2b = 0 Solving 3 + -2b = 0 Move all terms containing b to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2b = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2b = 0 + -3 -2b = 0 + -3 Combine like terms: 0 + -3 = -3 -2b = -3 Divide each side by '-2'. b = 1.5 Simplifying b = 1.5Solution
b = {-0.8181818182, 1.5}
| 2(x-7)-1=5(3x+1) | | 3x/5+2x=0 | | (t/8+5)=7 | | x=3x+7(x-8) | | -8=4(9-2)+4 | | 3x-x/8=30 | | 7-3r=r-4(5-2/5r) | | 6=4/5+5 | | -13=h-1 | | 0-4x+7=11 | | g(t)=3t-3 | | 2.8=6/4 | | f(x+8)=(x+8)2-3(x+8)-2 | | 0.3x^5+0.4x^4-8x^3-7x^2+23x+22=0 | | 3g-4=7g+12 | | 15=3n/5 | | -3/4+3=-12 | | 2p=5y | | b^2-b-9=0 | | 3/b-3-b/b-3 | | x/81=80/22 | | 3-b/b-3 | | 15+u= | | 4136/81=y | | r+4=-85 | | a/94=44/81 | | 10x^2-72x+12=0 | | r+5=-85 | | 38x-3x^2=4x^2-24 | | 8+2x=12+-6x | | 22/20=a/40 | | x/8=x/5+1/8 |